1998
DOI: 10.1093/hmg/7.12.1953
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of an ( 2-macroglobulin (Val1000lle) polymorphism and Alzheimer's disease

Abstract: alpha2-Macroglobulin (A2M) is a proteinase inhibitor found in association with senile plaques (SP) in Alzheimer's disease (AD). A2M has been implicated biochemically in binding and degradation of the amyloid beta (Abeta) protein which accumulates in SP. We studied the relationship between Alzheimer's disease and a common A2M polymorphism, Val1000 (GTC)/Ile1000 (ATC), which occurs near the thiolester active site of the molecule. In an initial exploratory data set (90 controls and 171 Alzheimer's disease) we not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
2
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(81 citation statements)
references
References 19 publications
4
71
2
4
Order By: Relevance
“…Several studies have demonstrated that LRP and its ligands, such as apolipoprotein E and ␣ 2 -macroglobulin, are associated with AD and alter A␤ metabolism (27)(28)(29)(30)(31)(32)(33)(34)(35). In this study, we demonstrated that a novel LDL receptor family member, LRP1B, which has high homology to LRP, can interact with APP and modulate its processing to A␤.…”
Section: Discussionmentioning
confidence: 61%
“…Several studies have demonstrated that LRP and its ligands, such as apolipoprotein E and ␣ 2 -macroglobulin, are associated with AD and alter A␤ metabolism (27)(28)(29)(30)(31)(32)(33)(34)(35). In this study, we demonstrated that a novel LDL receptor family member, LRP1B, which has high homology to LRP, can interact with APP and modulate its processing to A␤.…”
Section: Discussionmentioning
confidence: 61%
“…This exon is important because it encodes part of the bait region, where proteinases initiate reaction with ␣ 2 M by cleaving susceptible peptide bonds (15,16), and a segment of the growth factor binding sequence (17)(18)(19). In the second A2M gene polymorphism, Val-1000 is replaced by Ile (20). The linkage of A2M gene polymorphisms to late-onset AD remains incompletely understood, because the original observations have been confirmed in only a limited number of populations (21)(22)(23)(24)(25) and because there is no molecular explanation regarding how A2M gene mutations may affect ␣ 2 M structure, function, and expression.…”
mentioning
confidence: 99%
“…There seems that dimerization and LRP-1-ligand complex formation prevents the elimination of A 40 from the brain across the blood-brain barrier (Ito, et al 2007). There is also an over-representation of a common a2M polymorphism, Val1000 (GTC)/Ile1000 (ATC) in AD patients, which correlates with an increase in A burden (Kovacs 2000;Liao, et al 1998), further sustaining the importance of a2M in A clearance.…”
Section: Alpha2-macroglobulinmentioning
confidence: 99%